(untitled) (The Peerian Journal, 2022)
This article examines how systemic education affects training, young people, etc. Bringing a person to this potential, realizing his intellectual potential is the most important task of the education system. Today, without the introduction of a modern education system, it is impossible to train personnel in accordance with the requirements of the time